The Single Supervisory Mechanism Regulation: Questions of ne bis in idem and implications for the further integration of the system of fundamental rights protection in the EU. Issue 2 (April 2017) - van Bockel, Bas
This article discusses the enforcement framework of Regulation No. 1024/2013 (the Single Supervisory Mechanism Regulation, or 'SSMR') in light of the potential ne bis in idem situations which may arise, both in the interaction between the different modes and instruments of enforcement available to the European Central Bank (ECB) and National Competent Authorities (NCAs) under the SSMR, as well as in relation to national laws. 1 Shared enforcement of the rules for credit institutions under the SSMR transcends the familiar legal divide between the EU and the Member States, and the division of tasks and competences between national and EU authorities that is characteristic of EU law. The question raised here is whether the integrated enforcement architecture of the SSMR is matched by a sufficiently integrated system of fundamental rights protection in the EU, as viewed through the 'lens' of the ne bis in idem principle.